Odpowiedź :
a)(4x - 2)+(5x+3) = 4x-2+5x+3=9x+1
b)(y²+5y-6)+(2y²-y+8) = y²+5y-6+2y²-y+8= 3y²+4y+2
c)(5x²-ax+a²)+(3x²+2ax-3a²) = 5x²-ax+a²+3x²+2ax-3a²=8x²+ax-2a²
d)(10a(n)-2b(m)+c)+(3d(n)-6b(m)-c)= 10an-2bm+c+3dn-6bm-c=10an-8bm+3dn
b)(y²+5y-6)+(2y²-y+8) = y²+5y-6+2y²-y+8= 3y²+4y+2
c)(5x²-ax+a²)+(3x²+2ax-3a²) = 5x²-ax+a²+3x²+2ax-3a²=8x²+ax-2a²
d)(10a(n)-2b(m)+c)+(3d(n)-6b(m)-c)= 10an-2bm+c+3dn-6bm-c=10an-8bm+3dn
a)
(4x - 2)+(5x+3) = 20x² +12x - 10x -6 = 20x² + 2x - 6
b)
(y²+5y-6)+(2y²-y+8) = 2y⁴+ y³ + 8y² + 10 y³ - 5y² + 40y - 12 y² + 6y - 48 = =2y⁴+ 11y³ - 9y² + 6y -8
c)
(5x²-ax+a²)+(3x²+2ax-3a²) = 15gx⁴+ 10agx² +15ca²x² - 3agx³ - 2a²x² + 3a³x + 3ac²x² + 2a²x - 3a⁴= 15x⁴+9ax² + 18a²x² + 5a²x + 3a⁴
d)
(10a(n)-2b(m)+c)+(3a(n)-6b(m)-c)= (10an - 2bm + c )+(3an - 6bm - c) = 30a²n²- 60anbm - 10 anc - 6bman + 12b²m² + 2bmc + 3anc - 6bmc - c² = 30a²n² + 54 banm - 7anc + 12b²m² - 4 bmc - c²
(4x - 2)+(5x+3) = 20x² +12x - 10x -6 = 20x² + 2x - 6
b)
(y²+5y-6)+(2y²-y+8) = 2y⁴+ y³ + 8y² + 10 y³ - 5y² + 40y - 12 y² + 6y - 48 = =2y⁴+ 11y³ - 9y² + 6y -8
c)
(5x²-ax+a²)+(3x²+2ax-3a²) = 15gx⁴+ 10agx² +15ca²x² - 3agx³ - 2a²x² + 3a³x + 3ac²x² + 2a²x - 3a⁴= 15x⁴+9ax² + 18a²x² + 5a²x + 3a⁴
d)
(10a(n)-2b(m)+c)+(3a(n)-6b(m)-c)= (10an - 2bm + c )+(3an - 6bm - c) = 30a²n²- 60anbm - 10 anc - 6bman + 12b²m² + 2bmc + 3anc - 6bmc - c² = 30a²n² + 54 banm - 7anc + 12b²m² - 4 bmc - c²